Arthroscopic Repair of Chronic Bony Bankart Lesion Using a Low Anterior Portal - Jefferson C. Brand, M.D.; Paul Westerberg, M.A., A.T.C. (Arthroscopy Techniques, 2012)
We describe the repair of a chronic bony Bankart lesion in a case with recurrent instability using standard techniques and equipment for addressing anteroinferior glenohumeral instability. A 25-year-old man with recurrent instability and a chronic bony Bankart lesion with a Hill-Sachs lesion was treated. The inferior 2 sutures and knotless anchors are placed through a low anterior portal, which improves the angle of approach to the inferior portion of the glenoid that is fractured. The knotless anchors are impacted through the low anterior portal, just superior to the level of the suture, as the fragment tends to retract medially and inferiorly, with the drill guide slightly on the face of the glenoid. The superior-anterior portal adjacent to the biceps tendon gives a better view of the glenoid articular cartilage position of the anchors required to restore the anatomic location of the fracture fragment. The low anterior portal improved and simplified the reduction of the fracture fragment to the glenoid neck by allowing access to the anterior-inferior bony Bankart lesion that was repairable with suture and knotless anchors using standardized techniques.